EFL Learners' Knowledge of High-frequency Words in the Comprehension of Idioms: A Boost or a Burden?. (August 2019) - Park, Jinkyoung; Chon, Yuah V.
Single word items have usually been the unit of analysis for measuring L2 learners' vocabulary size, for designing word lists and for estimating word coverage of reading texts. However, what is lost in these estimates is the consideration of multiword expressions, such as idioms. To empirically test the assertion that the knowledge of single word items will not lead to automatic comprehension of multiword items, a two-part test was conducted on 124 Korean middle school learners of English: One was a test on idioms composed of the top 1, 000 words in English; the second tested single word items of the exact same words in the idiom test. Results indicated that the learners' knowledge of idioms was lagging behind that of single word items even when the learners knew most of the words that constituted the idioms. Differences between the learners' actual comprehension and reported comprehension level also indicated that the learners were overestimating their comprehension of the items. The comprehension strategies used to decode the meaning of idioms also indicated that guessing from context was the most effective strategy. Implications are discussed in the light of learning the idioms.